Analisis Potensi Pengembangan Perumahan dan Permukiman di Kecamatan Poasia Kota Kendari Berbasis Geographic Information System (GIS) - Iswandi Akbar; Ishak Kadir; Fajar Saranani (Jurnal Perencanaan Wilayah, 2022)
Population growth in urban areas affects the potential for housing and settlement development. This study aims to (1) analyze the suitability of the Regional Spatial Plan (RTRW) with zones that have the potential for housing and settlement development; and (2) Determine the potential for GIS-based housing and settlement development in Poasia District, Kendari City. The analytical methods used are qualitative analysis, GIS analysis, and overlay analysis. The results showed; (1) The suitability of the Regional Spatial Plan (RTRW) with the zone that has the potential for housing and settlement development in Poasia District, Kendari City, covering an area of 747.84 Ha; and (2) the results of the spatial analysis using the Geographic Information System found that the level of land potential to be developed into a housing and settlement area of 949.75 Ha, with sufficient potential for an area of 2,240.66 Ha and less potential for an area of 1,040.89 Ha or 0.74% . The area is quite potential with an area of 2,240.66 Ha and has limiting factors, namely insufficient availability of school services, water sources that are far enough away, insufficient road access is available and is located in a flooded area. The area with less potential is 1,040.89 Ha and has the main limiting factor, namely the limited availability of school services, road access and slopes that reach 15-25%. Keywords: Potential, Development, Housing and Settlements, and GIS Pertumbuhan penduduk di perkotaan mempengaruhi potensi pengembangan perumahan dan permukiman. Penelitian ini bertujuan (1) Menganalisa kesesuaian Rencana Tata Ruang Wilayah (RTRW) dengan zona yang berpotensi untuk pengembangan perumahan dan permukiman; dan (2) Menentukan potensi pengembangan perumahan dan permukiman berbasis GIS di Kecamatan Poasia Kota Kendari. Analisisnya adalah analisis kualitatif, analisis GIS, dan analisis overlay. Hasil penelitian menunjukkan; (1) Kesesuaian Rencana Tata Ruang Wilayah (RTRW) dengan zona yang berpotensi untuk pengembangan perumahan dan permukiman di Kecamatan Poasia Kota Kendari seluas 747,84 Ha; dan (2) Hasil analisis spasial dengan menggunakan Sistem Informasi Geografis bahwa tingkat potensi lahan untuk dikembangkan menjadi kawasan perumahan dan permukiman seluas 949,75 Ha, cukup berpotensi seluas 2.240,66 Ha dan  kurang berpotensi seluas 1.040,89 Ha atau 0,74%. Wilayah cukup berpotensi seluas 2.240,66 Ha memiliki faktor pembatas yaitu tidak cukup ketersediaan layanan sekolah, sumber air yang cukup jauh, akses jalan tidak cukup tersedia dan berada dalam kawasan banjir. Wilayah kurang berpotensi seluas 1.040,89 Ha memiliki faktor pembatas utamanya keterbatasan akan ketersediaan layanan sekolah, akses jalan dan kemiringan lereng yang mencapai 15-25% Kata Kunci : Potensi, Pengembangan, Perumahan dan Permukiman, dan GIS